2021
DOI: 10.1038/s41598-021-94590-x
|View full text |Cite
|
Sign up to set email alerts
|

The association of atherosclerotic cardiovascular disease and statin use with inflammation and treatment outcomes in tuberculosis

Abstract: Tuberculosis (TB) and atherosclerotic cardiovascular disease (ASCVD) have a close epidemiological and pathogenetic overlap. Thus, it becomes essential to understand the relationship between ASCVD and TB outcomes. From our retrospective cohort on drug-susceptible TB patients at the National Taiwan University Hospital, we assessed the association of pre-existing ASCVD (coronary artery disease (CAD) and atherothrombotic stroke (ATS)) with 9-month all-cause and infection-related mortality and the extent of mediati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Statins also have anti-inflammatory, antioxidant, antiproliferative and immunomodulatory effects (Bahrami et al 2018 ; Parizadeh et al 2011 ; Koushki et al 2021 ). Statins can stabilize atherosclerotic plaques and prevent platelet aggregation as well (Kim et al 2019 ; Chidambaram et al 2021 ). Statins are generally very well tolerated drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Statins also have anti-inflammatory, antioxidant, antiproliferative and immunomodulatory effects (Bahrami et al 2018 ; Parizadeh et al 2011 ; Koushki et al 2021 ). Statins can stabilize atherosclerotic plaques and prevent platelet aggregation as well (Kim et al 2019 ; Chidambaram et al 2021 ). Statins are generally very well tolerated drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) is a bacterial infection disease that mostly affects lung but, it could attack other parts of organs such as kidney, brain, and heart. Therefore, cardiac involvement in TB is common and TB infected patients possess a high risk to cause heart failure, constrictive pericarditis, or developing atherosclerotic cardiovascular diseases ( 24 , 25 ). The Cd74 (H-2 class II histocompatibility antigen gamma chain) included in TB pathway is reported that its expression on atherosclerotic plaques, and peripheral blood mononuclear cells (PBMC) with its potential pro-inflammatory responses ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, TB was associated with an increased risk of acute myocardial infarction (adjusted HR, 1.98; 95% CI, 1.3–3.0) [ 26 ]. Another study found that patients with atherosclerotic CVD had higher HR for all-cause and infection-related mortality after initiation of TB treatment [ 27 ]. Elevated serum markers of inflammation were found to mediate one-quarter to one-third of this association [ 27 ].…”
Section: Discussionmentioning
confidence: 99%